Estrategia didáctica para desarrollar proceso de enseñanza aprendizaje de valor posicional en niños de grado primero de primaria - Rodríguez Monsalve, Eliana (Universidad Antonio Nariño, 2023)
This degree work was carried out based on the development of four skills that favor numerical thinking (counting, partitioning, grouping and relationships between numbers), to promote the understanding of place value concept in first grade students, through a strategy of teaching-learning based on meaningful learning.